2023
DOI: 10.1101/2023.06.07.544021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CDK8 inhibitors antagonize HIV-1 reactivation and promote provirus latency in T cells

Abstract: Latent HIV-1 provirus represents a barrier towards a cure for infection, but is dependent upon the host RNA Pol II machinery for expression. We find that inhibitors of the RNA Pol II mediator kinases CDK8/19, Senexin A and BRD6989, inhibit induction of HIV-1 expression in response to latency reversing agents and T cell signaling agonists. These inhibitors were found to impair recruitment of RNA Pol II to HIV-1 LTR. HIV-1 expression in response to several latency reversal agents was impaired upon disruption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
2
3
0
Order By: Relevance
“…4 A , 4 B ). In agreement with previous reports (Horvath et al , 2023), we observed a vigorous synergistic interaction between PEP005 activation of NFκB and IACS-9571 inhibition of the TRIM24 bromodomain (Fig. S3).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…4 A , 4 B ). In agreement with previous reports (Horvath et al , 2023), we observed a vigorous synergistic interaction between PEP005 activation of NFκB and IACS-9571 inhibition of the TRIM24 bromodomain (Fig. S3).…”
Section: Resultssupporting
confidence: 93%
“…The function of CDK8/19 is not dependent on Tat (Fig 5, Fig. S4), consistent with previous findings that CDK8/19 inhibition limits reactivation of ACH2 and U1 proviral latency cell models (Horvath et al , 2023). Additionally, we display a synergistic interaction between the CDK8/19 inhibitor Senexin A and inhibitors of either CDK7 or CDK9, suggesting distinct mechanism(s) of action.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations